Pemikiran Wahid Hasyim tentang Pendidikan dan Relevansinya dengan Dunia Modern - Nurhabibah . (LITERASI (Jurnal Ilmu Pendidikan), 2018)
KH Wahid Hasyim is a figure of clergy and statesman who is undoubtedly his service to the state. As a cleric, he is son of KH Hasyim Asy’ari, the founder of Nahdatul Ulama, the largest Islamic organization in Indonesa. As a statesman, he served as a minister of  religion. His work in the academic world and his struggle and educating the people is well known and made an impression. In outlining the policy in the world of education, certainly not apart from the Islamic backround and statesmanship he has. This make his thinking to be balanced between the inner and outer dimensions, between traditionality and modernity. This paper attemps to decipher Wahid Hasyim’s biography and the examines his thoughts in education as well as his relation to education in the modern world. The significance of this paper is as a literature for the biography of Wahid Hasyim and the relevance of his thought to education from time to time.Keyword: Wahid Hasyim, education, modern